2008
DOI: 10.1128/jcm.00871-08
|View full text |Cite
|
Sign up to set email alerts
|

Subtype-Specific Suppression of Shiga Toxin 2 Released from Escherichia coli upon Exposure to Protein Synthesis Inhibitors

Abstract: Shiga toxins (Stx) are important virulence factors in the pathogenesis of severe disease including hemolyticuremic syndrome, caused by Stx-producing Escherichia coli (STEC). STEC strains increase the release of Stx in vitro following the addition of fluoroquinolones, whereas protein synthesis inhibitors previously have been reported to suppress the release of Stx. The amount of Stx released from wild-type STEC strains incubated with protein synthesis inhibitors was examined by a Vero cell cytotoxicity assay. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
17
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 22 publications
(31 reference statements)
2
17
0
Order By: Relevance
“…4). These results support previous studies which demonstrated that antibiotics that inhibited protein synthesis decrease toxin production in vitro (25,38,39). Furthermore, two studies have shown that AZM affords protection from Stx-mediated disease in vivo.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…4). These results support previous studies which demonstrated that antibiotics that inhibited protein synthesis decrease toxin production in vitro (25,38,39). Furthermore, two studies have shown that AZM affords protection from Stx-mediated disease in vivo.…”
Section: Discussionsupporting
confidence: 81%
“…Some studies report antibiotic treatment of patients with STEC infection to be beneficial and others do not (reviewed in reference 23). Similarly, studies examining the ability of antibiotics to promote Stx production in vitro have given mixed results (9,13,18,21,25,37). In several studies Stx expression was assessed by enzyme-linked immunosorbent assay (ELISA), Western blotting, or mRNA levels, and these indirect assays may not accurately reflect levels of biologically active Stx, since not all subunits may be part of assembled functional AB 5 complexes.…”
mentioning
confidence: 99%
“…There are conflicting reports regarding its effect on release of both Stx1 and Stx2. One study reported its increasing effect on toxin release from STEC (Grif et al, 1998); however, the recent studies demonstrated suppression in toxin release from STEC carrying stx2 upon exposure to MIC or sub-MIC of gentamicin (Pedersen et al, 2008). We found a considerable decrease in Stx release at MIC and sub-MIC of gentamicin.…”
Section: Discussionmentioning
confidence: 75%
“…Although the exact mechanism of toxin suppression remains to be revealed, it has been proposed that the decrease in toxin amount could be due to inhibition of protein synthesis, as some antibiotic molecules attach to the membrane-bounded ribosome involved in protein synthesis (Shibl, 1984). The suppression of late gene promoter of stx gene in case of protein synthesis inhibitor (gentamicin) is also reported, promising use of these agents in STEC infections (Pedersen et al, 2008).…”
Section: Discussionmentioning
confidence: 98%
“…However, the effects of different antibiotic classes on Stx production in vitro differ and are also dependent on the antibiotic concentration and the nature of the EHEC strain (e.g., O group or Stx type) (16,22,24,28,29,39). In studies performed with EHEC O157:H7, fluoroquinolones, trimethoprim-sulfamethoxazole, and ampicillin significantly increased Stx2 production (16,20,22,23,24,29,39,40), whereas macrolides (24,29,39), carbapenems (22,23), aminoglycosides (22,24), rifampin (31), rifaximin (28), and fosfomycin (22,24,40) either had no effect on Stx2 production or suppressed it. These in vitro data are in accordance with experiments with animal models (31,39,40).…”
mentioning
confidence: 99%